Pengaruh pay transparency terhadap job satisfaction, turnover intention, dan organizational commitment serta perceived organizational support sebagai variabel mediasi - Wati, Diyana; Putra, Andreas Wahyu Gunawan; Tanuwijaya, Justine (Universitas Widya Mataram, 2024)
This study aims to investigate the effect between pay transparency and Perceived Organizational Support and its impact on job satisfaction, turnover intention, and organizational commitment. This study was conducted at PT XYZ by involving employee respondents in various divisions. The research method used was a survey using a questionnaire as a data collection instrument. The research sample consisted of 136 respondents using a saturated sample. Data analysis was performed using descriptive statistical techniques and SEM. The results of the study show that there is a significant relationship between pay transparency and Perceived Organizational Support. This finding indicates that the level of payroll transparency in an organization influences the support felt by employees for the organization. Furthermore, Perceived Organizational Support was also found to have a positive and significant relationship with job satisfaction, turnover intention, and organizational commitment. In addition, this study also reveals that pay transparency has a significant effect on job satisfaction through Perceived Organizational Support. That is, payroll transparency can affect the level of job satisfaction through the level of organizational support felt by employees.